Pengaruh Asimetri Informasi, Manajemen Laba, Pengungkapan Sukarela dan Diversifikasi Bisnis terhadap Biaya Modal Ekuitas - Muhammad Hamid; Irawan Irawan; Dewi Zakia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study analyzes the factors that influence the cost of equity capital in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the period 2020–2023. The study focuses on information asymmetry, earnings management, voluntary disclosure, and business diversification as determinants of the cost of equity capital. This study is relevant to the dynamics of the financial market after the decline in Bank Indonesia's benchmark interest rate in the 2024–2025 period, which has the potential to change investor preferences and increase attention to the quality and transparency of company information. The study uses a quantitative approach with secondary data obtained from companies' financial statements and annual reports. The sample was determined using purposive sampling and resulted in 177 observations from 46 companies over four years of observation. The cost of equity capital was measured using the Ohlson model, while hypothesis testing was conducted using multiple linear regression analysis. The results show that earnings management and voluntary disclosure have a significant effect on the cost of equity capital. Conversely, information asymmetry and business diversification were not found to have a significant effect. These findings confirm that the quality of financial reporting and the level of information disclosure play an important role in shaping investors' risk perceptions and return expectations.